Cross-Cultural Competence in Pre-Service Teacher Education Towards Global Awareness: A Study in a Pakistani Context - Jamil, Bushra; Shaoan, Mirajur Rhaman; Irfan, Sadia; Arif, Muhammad; Okafor, Miracle Uzochukwu; Zeyuan, Yu (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Due to globalization, cultural awareness has been recognized as an essential factor in the context of teacher-education programs. The current research focuses on the role of cross-cultural training in increasing teachers' readiness for multicultural classrooms in Pakistan. This study employed a mixed-methods approach, collecting both quantitative and qualitative data through surveys and interviews with pre-service teachers. This investigation established a positive relationship between cross-cultural training, cultural diversity knowledge, and teacher self-efficacy in handling diversity. In addition to the above, regression analysis also confirmed that all these factors collectively explain a significant proportion of the variations in teacher preparedness. They integrated cross-cultural competencies in teacher-education curricula to prepare future instructors for diverse learners. The following recommendations are necessary to enhance the quality of teacher-preparation programs: the adoption of standardized assessments, the integration of fieldwork experiences, and regular professional development for teachers. This research contributes to the growing body of literature that advocates for a more cohesive approach to multicultural education, highlighting its significance in the educational process.